A DESCRIPTIVE STUDY OF AUSTRALIAN-ENGLISH PRONUNCIATION OF VOWEL AND DIPHTHONG SOUNDS - FEVRIYANTI, ELVERA (2009)
The research paper aims to figure out kinds of Australian English sounds and the differences between Australian English accent and British English one used in Australian movie. The data of this research are in the form of words taken from Australian movie. This research is a descriptive-qualitative study, which uses technique of collecting, classifying, and analyzing, then drawing conclusion. In analyzing the kinds of Australian English pronunciation and accent, the researcher refers to the Australian English sound system. To describe the difference between Australian English accent from British English accent, the researcher employs the distributional method, especially in substitutional method and extention method. The result of the study shows that first, the kinds of Australian English sounds are two diphthong and five vowels sounds that are used in Australian English sound, they are: [ɑe], [æɔ], [æ], [i:], [ɐ], [ɔ], and [ʉ:]. Second, the difference between Australian English Accent and British English one is in the form of the position of the lip, mouth, tongue, low jaw, nasalisation, long and short pronunce, etc. Mostly, the vowel sound used in Australian English is diphthong of [ɑe] sound.